KAPASITAS JENUH INSTALASI PENGOLAHAN AIR LIMBAH DENPASAR SEWERAGE DEVELOPMENT PROJECT (DSDP) - Nadiasa, Mayun (Jurnal Ilmiah Teknik Sipil; Vol. 15, No. 2 Juli 2011, 2012)
Bali Province government had performed Denpasar Sewerage Development Project (DSDP) to anticipate pollution in rivers, ground water/public well and coastal areas caused by wastewater sewage in Denpasar, Sanur and Kuta. First phase of construction had completed and begun the operational in 2008 with public service agencies or Badan Layanan Umum Pengelola Air Limbah (BLUD PAL) as the authorized organization to manage the project implementation. In this research, population and buildings were predicted using its function in service area and estimated by trend linier method that results in optimum capacity. Wastewater Treatment Plant Capacity of the DSDP project in Phase I is 51,000m3/hr. In 2007, the waste produced by the citizen in the service area is 40,777.41m3/day. In fact, this number of waste has increased continously together with the development of the service area, so that in 2020 the capacity of wastewater treatment will be in excessive amount, which is 51,843.54m3/day. Therefore, the development of IPAL is significantly required to fulfill an increasing demand of treatment capacity.
Keywords: wastewater tretament, pollution, wastewater sewage